Risk of Falling level in Stroke Patients at dr. Soekardjo Hospital, Tasikmalaya - Asep Robby; Teti Agustin; Dika Awalia (LP3M Universitas Muhammadiyah Tasikmalaya, 2023)
Stroke is a disease of blood vessels in the brain. This occurs when the blood supply to the mind is reduced or obstructed for some reason, which triggers an unexpected lack of oxygen at the synapses. The risk of falling is a patient who is in danger of falling which is generally caused by ecological and physiological variables that can cause injury. This study aims to assess the level of risk of falling in stroke patients in Melati Room 2B RSUD dr. Soekardjo City of Tasikmalaya. The research method uses a quantitative descriptive method. The study population was stroke patients undergoing treatment in the Melati 2B room at RSUD dr. Soekardjo Tasikmalaya with accidental sampling technique of 12 respondents. The research was conducted on April 28 - May 7 2022. The data collection instrument used the Morse Fall Scale and the Geriatric scale. The results showed that 50% of respondents were categorized as having a low risk of falling, 33.3% being at moderate risk of falling, and 16.7% with a high risk of falling. Based on these results, it is suggested that nurses periodically conduct fall risk assessments to avoid injury to stroke patients because there is still a risk of falling injury to patients treated in that room.